Let's describe a polymer as a linear chain of $N$ links which all have a bendable part. The energies of one link are $\epsilon_-$ (unbended) and $\epsilon_\wedge$ (bended). Additionally, the lengthsof a single link are given by $l_-$ (unbended) and $l_\wedge < l_-$ (bended).

With this information, I want to compute the canonical partition function for a given length $L$ of the polymer:

$$Z(T,L,N) = \sum_\text{states $n$} e^{-\beta E_n}$$

with $N$ the total number of links in the chain and $\beta = \frac{1}{kT}$. $L$, $N$ and the number of bended links $N_\wedge$ are not independent, so the sum runs over all states which satisfy the relation which connects $L$, $N$ and $N_\wedge$.

My problem is that I have no idea how to tackle this. I tried to express the total energy and length by

$$E = N\epsilon_- + N_\wedge(\epsilon_\wedge-\epsilon_-)\qquad\text{and}\qquad L = Nl_- + N_\wedge(l_\wedge-l_-)$$

but this still leaves me with the question how to evaluate the sum for the partition function. Can anybody help me with this?


You can connect the equations for $E$ and $L$ by using $$N=n_{\wedge}+n_-$$

Write $L$ as: $$L=n_-(l_--l_{\wedge})+Nl_{\wedge}=d n_-+Nl_\wedge$$ and $E$ as: $$E=n_-(\epsilon_--\epsilon_\wedge)+N\epsilon_\wedge=f n_-+N\epsilon_\wedge$$

Where $d=l_--l_\wedge$ and $f=\epsilon_--\epsilon_\wedge$

Now use the equation for $L$ to write $n_-$ in terms of $L$ and $N$: $$n_-=\frac{L-Nl_\wedge}{d}$$ Insert this into the equation for the energy of a certain configuration: $$E=\frac{f(L-Nl_\wedge)}{d}+N\epsilon_\wedge$$

And we can now write the equation for the partition function in terms independent of the sum over states: $$Z=\sum_{\mathrm{states} \ i}exp\Bigl\{-\beta\Bigl(\frac{(L-Nl_\wedge)f}{d}+N\epsilon_\wedge\Bigr)\Bigr\}=exp\Bigl\{-\beta\Bigl(\frac{(L-Nl_\wedge)f}{d}+N\epsilon_\wedge\Bigr)\Bigr\}\sum_{\mathrm{states} \ i}1$$ We just need to count the ways that the kinks and straights can be arranged. Imagine the chain completely straightened out. We want to distribute $n_\wedge$ kinks over $N$ positions. There are: $$\frac{N!}{n_\wedge!(N-n_\wedge)!}=\frac{N!}{n_\wedge!n_-!}=\frac{N!}{\frac{L-Nl_-}{d}!\frac{L-Nl_\wedge}{d}!}$$ ways to do this. So in full, you have the partition function: $$Z(T, N, L)=\frac{N!}{\frac{L-Nl_-}{d}!\frac{L-Nl_\wedge}{d}!}exp\Bigl\{-\beta\Bigl(\frac{(L-Nl_\wedge)f}{d}+N\epsilon_\wedge\Bigr)\Bigr\}$$

This is easier to write if you change from a function of $L$ to a function of $n_-$ (They contain the same information): $$Z(T, N, n_-)=\frac{N!}{n_-!(N-n_-)!}exp\Bigl\{-\beta\Bigl(n_-f+N\epsilon_\wedge\Bigr)\Bigr\}$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.